Exploring Factors Influencing Consumer Purchase Intention from Social Media Advertisements: an Exploratory Factor Analysis Approach - Salsabila, Ananda Humaira Putri; Qastharin, Annisa Rahmani (Proceedings International Conference on Education Innovation and Social Science, 2023)
Over the past few years, the use of social media advertising by businesses has experienced significant growth, offering unprecedented opportunities for effective marketing and reaching target audiences. Despite this growth, Codykit's social media advertising efforts for their product, Codyplay, in the Indonesian children's book industry have not achieved the desired sales conversion rate and have resulted in a high customer acquisition cost (CAC). Therefore, this research aims to investigate the different elements of social media advertising that has the ability to drive customer purchase intention. The goal is to enhance the online sales traffic of Codyplay and improve the overall effectiveness of social media advertising efforts for Codykit. The research involved conducting a survey and utilizing exploratory factor analysis method to reduce the number of variables, detect the structure of the relationship between variables, and classify them into a new group of variables consisting the specific characteristics that significantly influence how people perceive social media advertisements. The survey respondents are Codykit's target market, specifically mothers with children aged 4-7 years old residing in Jabodetabek, Bandung, and East Java, who had previously made online purchases of children's goods. The findings indicate that engagement drivers, celebrity influence, emotive impulse, and innovative persuasion all have an impact on how social media advertising is evaluated. By placing sufficient emphasis on these specific traits, it would be possible to develop effective social media marketing strategies and increase consumer buying intent.